Pengolahan bahan perpustakaan di UPT Perpustakaan IAIN Kediri - Evi Rahmawati (IJAL (Indonesian Journal of Academic Librarianship), 2021)
The processing of library materials is an integral part of supporting the implementation of library service activities. In processing library materials, it is necessary to apply international rules and principles. This study aims to determine and describe how the processing of library materials at the Library of IAIN Kediri. This research uses qualitative research methods with a case study approach. The steps in this research are through the data and literature collection stage, the analysis stage, the data presentation stage, and the conclusion drawing stage. The conclusion in this study, namely cataloguing library materials, has followed the rules that apply internationally in cataloguing library materials. The obstacles experienced by the UPT Library of IAIN Kediri in processing library materials are the lack of human resources who have library science qualifications, the lack of human resources for librarians who master the technical skills of processing library materials, and the lack of infrastructure in the library material processing activities.